Study of cytokine induced neuropathology by high resolution proton NMR spectroscopy of rat urine. - Griffin, J; Anthony, D; Campbell, S; Gauldie, J; Pitossi, F; Styles, P; Sibson, N (2004)
Multiple sclerosis is a major cause of non-traumatic neurological disability. The identification of markers that differentiate disease progression is critical to effective therapy. A combination of NMR spectroscopic metabolic profiling of urine and statistical pattern recognition was used to detect focal inflammatory central nervous system (CNS) lesions induced by microinjection of a replication-deficient recombinant adenovirus expressing TNF-alpha or IL1-beta cDNA into the brains of Wistar rats. These animals were compared with a group of naïve rats and a group of animals injected with an equivalent null adenovirus. Urine samples were collected 7 days after adenovirus injection, when the inflammatory lesion is maximally active. Principal components analysis and Partial Least Squares-Discriminate analysis of the urine (1)H NMR spectra revealed significant differences between each of the cytokine adenovirus groups and the control groups; for the TNF-alpha group the main differences lay in citrate and succinate, while for the IL-1beta group the predominant changes occurred in leucine, isoleucine, valine and myo-inositol. Thus, we can identify urinary metabolic vectors that not only separate rats with inflammatory lesions in the brain from control animals, but also distinguish between different types of CNS inflammatory lesions.